Kesesuaian Kurikulum Merdeka dengan Kurikulum Deep Learning - Wathon, A (Lembaga Yasin AlSys, 2024)
This study aims to assess the suitability between the Independent Curriculum and the Deep Learning Curriculum in the context of education in Indonesia. This problem stems from the rapid development of information technology and the increasing need for digital skills in the modern era. The approach used in this study is a comparative descriptive analysis of the structure and objectives of the Independent Curriculum and the principles and implementation of the Deep Learning Curriculum. The results of the study indicate that the Independent Curriculum, which focuses on students' learning freedom and improving the quality of learning, is in line with the principles of the Deep Learning Curriculum. These principles include the use of technology in the learning process, a project-based learning approach, and the development of critical and creative thinking skills. However, there are several aspects that need more attention, such as increasing the integration of technology into learning, teacher training to support the implementation of the Deep Learning Curriculum, and evaluation that is more focused on measuring students' skills and understanding in the context of technology. Thus, this study shows that the Independent Curriculum can be optimized through the application of the concepts and principles of the Deep Learning Curriculum. This aims to improve the quality of education in Indonesia so that it is in line with the demands of the ever-growing digital era.